2010
DOI: 10.1002/jcu.20714
|View full text |Cite
|
Sign up to set email alerts
|

Cystic change in thyroid carcinoma: Prevalence and estimated volume in 360 carcinomas

Abstract: The vast majority (88%) of thyroid cancer is uniformly solid or has minimal (1-5%) cystic change by sonography. Marked cystic change (>50% of the nodule) occurred in only 2.5% of cancers, which had other sonographic findings worrisome for malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
3
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 16 publications
2
38
3
2
Order By: Relevance
“…Furthermore, if the solid component is hypoechoic, is lobulated, has an irregular border or punctate echogenic foci line, or has vascular flow, the risk for malignancy is increased. If the solid component is isoechoic, is centrally located within the nodule or, if peripheral, has no acute angle with the nodule wall, or has a smooth margin, spongiform appearance, or comet tail artifacts, it is likely benign [13,14]. n Purely cystic nodules or spongiform nodules have a very low risk for malignancy [6].…”
Section: Background and Significancementioning
confidence: 98%
“…Furthermore, if the solid component is hypoechoic, is lobulated, has an irregular border or punctate echogenic foci line, or has vascular flow, the risk for malignancy is increased. If the solid component is isoechoic, is centrally located within the nodule or, if peripheral, has no acute angle with the nodule wall, or has a smooth margin, spongiform appearance, or comet tail artifacts, it is likely benign [13,14]. n Purely cystic nodules or spongiform nodules have a very low risk for malignancy [6].…”
Section: Background and Significancementioning
confidence: 98%
“…Thyroid cancers usually appear solid, but those with predominant cystic changes (>50% of the nodule) can be observed in 2.5%-6% of all thyroid cancers [1,2]. Cystic papillary thyroid cancer (PTC) commonly shows the presence of tridimensional fragments, anisonucleosis, nuclear bars, pseudoinclusions, powdery chromatin, cytoplasmic vacuoles, metaplastic cytoplasm, and autolysis on cytologic specimens [3].…”
Section: Introductionmentioning
confidence: 99%
“…Solid consistency is more common in malignant thyroid nodules and the vast majority (82% -91%) of thyroid cancers are solid (10)(11)(12). In a study including 360 consecutively surgically removed thyroid cancers, 88% were reported to be solid or minimally cystic (13). It is suggested that malignancy rate is higher in predominantly solid than mixed solid/cystic nodules, while cystic 8…”
Section: Discussionmentioning
confidence: 99%